Development and Research Status of Key Technology of Land Gas Turbine Gearbox in China - Yuan Guangqian; Li Jinku; Hu Yunbo (Jixie chuandong)
Gas turbine is a new generation of clean energy power plant with high power，high efficiency，small size and long life. Gas turbine gearbox is a device that transfers the output power of gas turbine to the working machine after deceleration and torsion increase，and it is one of the key supporting systems of gas turbine units. The development status of gas turbine and gas turbine gearbox at home and abroad is described. The typical structure of gas turbine gearbox and its advantages and disadvantages are analyzed and enumerated. The key technologies and research status of gas turbine gearbox development，such as transmission system dynamics research，planetary gear load sharing technology and gear modification technology，are summarized. The development trend of gas turbine gearbox and the problems needing further research are pointed out.